Digital therapeutics: a systematic review of clinical trials characteristics. (14th October 2021) - Santoro, E; Boscherini, L; Caiani, E G
Abstract: Introduction: Digital therapeutics (DTx) are a subset of digital health tools delivering evidence-based therapeutic interventions that are driven by high quality software programs to prevent, manage, or treat a medical disorder or disease. They are studied using randomized clinical trial methodology and reviewed, cleared or certified by regulatory bodies as required to support product claims regarding risk, efficacy, and intended use. Purpose: To perform a systematic review of clinical research/studies conducted in the field of DTx with the aim to describe studies where DTx were used, classifying them by digital intervention and condition, and analysing and reporting the characteristics of clinical trials. Methods: The U.S. National Library of Medicine ClinicalTrials.gov was searched using the terms "digital therapeutics", "digital therapeutic", "digital therapy", and "digital therapies" within the fields "Intervention/treatment" and "Title/Acronym", and the resulting trial characteristics were extracted and analysed. Results: In total, 560 clinical trials were retrieved on January 10, 2021. Most of them (n=424, 75.7%) were excluded because they were observational studies (n=82), non-randomized/single arm assignment studies (n=123), not involving any digital health tool (n=181), or involving digital health tools not classified as DTx (n=38). Of the remaining 136 trials, the DTx intervention was delivered through apps (n=57, 41.9%), web-based systems (n=35, 25.7%), videogames (n=12, 8.8%), virtual reality (n=6, 4.4%), text messages (n=5, 3.7%), social media platform (n=4, 2.9%), computer-based systems (n=3, 2.2%), or other (n=14, 10.3%), and applied to the following clinical scenarios: mental health (n=47, 34.6%), chronic pain and chronic diseases (n=26, 19.1%), smoking and other substances abuse or addiction (n=17, 12.5%), insomnia and sleeping disorders (n=12, 8.8%), obesity and physical activity (n=11, 8.1%), cardiovascular diseases (n=10, 7.3%), and other conditions (n=13, 9.6%). Apps were used more frequently for chronic pain (54%) and sleeping disorders (67%), while videogames and web-based systems were adopted for mental health in 21.3% and 38% of the trials, respectively, and text messages were preferred in 18.2% of obesity and 17.6% of addiction trials, respectively Sixty-eight trials (50%) started in the last three years (2019, 2020, and 2021), while 54.4% were ongoing, 33.8% completed, 2.9% stopped early, and 8.8% with status unknown. Conclusions: The term "digital therapeutics" was very often incorrectly used by researchers when they register their trials in ClinicalTrials.gov, improperly including studies involving the use of digital health tools to support a drug intake or monitor a condition. Mobile apps, web-based systems and videogames were the most adopted technologies to deliver DTx, while mental health diseases, chronic pain, and addiction were the conditions in which they were most frequently studied. Funding Acknowledgement: Type of funding sources: None.